Implementation of the merdeka curriculum for competency achievement and graduate employability in vocational education - Agus Fadly Taqwan Lubis; Asnil Asnil; Oriza Candra; Bambang Heriyadi (Global Econedu, 2026)
This study aimed to analyze the implementation of the Merdeka Curriculum, students' competency achievement, graduate employment outcomes, and the supporting and constraining factors at Tritech Informatics Private Vocational High School, Medan. A qualitative descriptive case study was conducted using semi-structured interviews with nine purposively selected informants, classroom observations, and document analysis, including students' academic records, Vocational Competency Test (VCT) results (2022–2025), and graduate tracer study data (2022–2024). The findings showed that competency-based learning, authentic assessment, and industry collaboration were effectively implemented. Students' average academic achievement increased from 85.28 to 89.31, while VCT scores improved from 87.97 to 93.54. Tracer study data revealed that 88.8% of graduates engaged in productive activities, with increasing employment rates and occupational relevance. The Merdeka Curriculum contributed positively to competency development and graduate employability, although continuous improvements in teacher competence, learning facilities, and industry partnerships remain essential.